Black holes and baby universes and other essays - Hawking, S. W. (Stephen W.) (New York : Bantam Books, 1994)
Includes thirteen essays ranging from the autobiographical to the purely scientific. Discusses imaginary time and black holes while reflecting on will, the value of life, and his perceptions of death.
Oxford and Cambridge -- My experience with ALS -- A brief history of a brief history -- Is the end in sight for theoretical physics? -- The quantum mechanics of black holes -- The future of the universe.
Includes index.
Wilson's Senior High School.
Adult
Keywords: Hawking, S. W; Hawking, S. W; Cosmology; Physicists -- Great Britain -- Biography; Science -- Philosophy; Physicists -- Biography; Science -- Philosophy; Universe